PENGARUH KAPASITAS PENYERAPAN TERHADAP KINERJA INOVASI DI LEMBAGA PEMASYARAKATAN KELAS IIA BENGKULU - Astri Aminatu Rizqi; Kasmiyanti (Jurnal Komunikasi Hukum, 2024)
This research aims to examine the influence of Absorptive Capacity on Innovation Performance in Class IIA Bengkulu Correctional Institutions. Using quantitative research methods, data was collected from 117 Class IIA Bengkulu prison employees through questionnaires. Data analysis was carried out using a simple linear regression test using SmartPLS 4.0, which showed a positive and significant influence between Absorptive Capacity and Innovation Performance. The research question focuses on whether there is an influence of Absorptive Capacity on Innovation Performance in Class IIA Bengkulu Correctional Institutions. The aim of the research is to understand and assess these influences. The practical benefits of research involve the Technical Implementation Unit, researchers and other parties, by providing related input.